Disparity in chromosomal variation within the Apiomorpha minor species-group - Mills, P.J.; Cook, L.G. (ENTOMOLOGIA HELLENICA, 2010)
The scale insect genus Apiomorpha is one of the most chromosomally diverse of all animal genera, with diploid complements ranging from 4 to 192. There is even considerable variation within many of the 41 described species. For example, variation within the A. minor speciesgroup (A. minor, A. sessilis and A. annulata) shows an extraordinary range with counts from 2n = 4 through to 2n = 84. However, much of this variation is within a single currently recognized species – A. minor. In contrast, another species in the A. minor species group, A. sessilis, has been reported to have only counts of 2n = 4. To determine whether the reported lack of variation within A. sessilis was due to limited sampling, we collected specimens from across its known range of more than 1,100 km in eastern Australia. We did not find any additional chromosome counts for A. sessilis, confirming the constancy of karyotype in this species. This suggests the question "why does A. sessilis have such a conserved karyotype throughout its range while A. minor is so diverse?”